The Welch Emotional Connection Screen: validation of a brief mother–infant relational health screen. (13th August 2018) - Hane, Amie A.; LaCoursiere, Jasmine N.; Mitsuyama, Mai; Wieman, Sarah; Ludwig, Robert J.; Kwon, Katie Y.; V. Browne, Joy; Austin, Judy; M. Myers, Michael; Welch, Martha G.
Abstract: Aim: The Welch Emotional Connection Screen (WECS), assesses mother–infant Emotional Connection in clinical settings. It includes: Attraction, Vocal Communication, Facial Communication, Sensitivity/Reciprocity and clinical decision of Emotional Connection (yes/no). We tested concurrent and construct validity of the WECS and associations with behavioural and physiological measures in preterm infants. Methods: Videos from 76 mothers–infants (gestational age 36 weeks) during an in‐NICU caregiving paradigm were coded for maternal caregiving behaviour. Videos of mothers–infants were also obtained at 4 months during 10 minutes of face‐to‐face play (coded with WECS and for maternal positivity and infant social engagement) and the still‐face paradigm (coded for infant behavioural approach towards mother; infant electrocardiogram acquired in vivo ). Results: WECS maternal scores were positively associated with maternal sensitivity and quality of vocal contact at 36 weeks (caregiving) and maternal positivity at 4 months (face‐to‐face). WECS infant scores positively correlated with infant social engagement and maternal positivity during face‐to‐face interactions at 4 months. Infants from emotionally not connected dyads (vs. emotionally connected dyads) displayed autonomic dysregulation and less approach‐seeking behaviour towards mother during interactive/play sessions of the still‐face paradigm. Conclusion: This preliminary evidence supports the WECS as a valid screen for rating mother–preterm infant emotional connection associated with healthier infant biobehavioural stress responding.